2019
DOI: 10.1017/s0033291719002344
|View full text |Cite
|
Sign up to set email alerts
|

Depressive psychopathology in first-episode schizophrenia spectrum disorders: a systematic review, meta-analysis and meta-regression

Abstract: BackgroundDespite knowing for many decades that depressive psychopathology is common in first-episode schizophrenia spectrum disorders (FES), there is limited knowledge regarding the extent and nature of such psychopathology (degree of comorbidity, caseness, severity) and its demographic, clinical, functional and treatment correlates. This study aimed to determine the pooled prevalence of depressive disorder and caseness, and the pooled mean severity of depressive symptoms, as well as the demographic, illness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 77 publications
(106 reference statements)
3
34
0
Order By: Relevance
“…It is also posited that depressed patients have higher tendency of negative self-appraisal, which may lead to their lower satisfaction with various life domains, particularly psychological wellbeing (Renwick et al, 2012). Importantly, given that depression represents a major determinant of SQoL and is prevalent in the early phase of illness (Herniman et al, 2019), comprehensive evaluation and regular monitoring of depressive symptoms should be integrated in EI service to facilitate early detection and intervention which will in turn promote patients' SQoL. Alternatively, our analysis found that patients with younger age at onset of psychosis exhibited poor SQoL trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…It is also posited that depressed patients have higher tendency of negative self-appraisal, which may lead to their lower satisfaction with various life domains, particularly psychological wellbeing (Renwick et al, 2012). Importantly, given that depression represents a major determinant of SQoL and is prevalent in the early phase of illness (Herniman et al, 2019), comprehensive evaluation and regular monitoring of depressive symptoms should be integrated in EI service to facilitate early detection and intervention which will in turn promote patients' SQoL. Alternatively, our analysis found that patients with younger age at onset of psychosis exhibited poor SQoL trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mood symptoms, including depression and mania, is common in schizophrenia, as is the presence of positive symptoms in bipolar disorder. Diagnostic fluidity is a key component in first-episode psychosis; mood symptoms such as depression are particularly common in this early phase of illness (Herniman et al, 2019; Upthegrove et al, 2017). While the majority of first-episode psychosis patients would meet diagnostic criteria for schizophrenia, for those patients without a clear schizophreniform presentation making a diagnosis is still essential for effective and prompt treatment (Marshall et al, 2014), as reviewed in the section on First-episode psychosis above, and multidisciplinary teams should be prepared to make and then if necessary change a diagnosis as the clinical presentation becomes clearer.…”
Section: Pharmacological Strategies For Comorbid Affective Disordermentioning
confidence: 99%
“…Depression was also the dependent variable for the SCZ subjects because, while positive and negative symptoms are more common endpoints in trials for SCZ, self-report measures for these symptoms are not well-established or commonly used. Further, depression is highly prevalent (40-60%), associated with an array of poor clinical outcomes, and a common treatment target throughout the course of SCZ [31,32]. The BDI has been extensively used in both MDD and SCZ and shows strong correlations with standard clinician reported depression outcome measures [33,34].…”
Section: Assessmentsmentioning
confidence: 99%